PENGARUH STORE ATMOSPHERE, PROMOSI PENJUALAN DAN KELENGKAPAN PRODUK TERHADAP IMPULSE BUYING: (STUDI PADA KONSUMEN TOSERBA MITRA KARTASURA) - Antonia, Shunia Dwi; Sulistyowati, Pemilia (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to determine and analyze the direct influence of store atmosphere on impulse buying in Consumers of Kartasura Mitra Department Store, to determine and analyze the direct influence of sales promotion on impulse buying in Consumers of Kartasura Mitra Department Store, to determine and analyze the direct influence of product completeness on impulse buying in Consumers of Kartasura Mitra Department Store and to determine and analyze the simultaneous influence of store atmosphere, sales promotion, product completeness on impulse buying in Consumers of Kartasura Mitra Department Store. This study uses a quantitative method with a sample of 100 employee respondents at Consumers of Kartasura Mitra Department Store. Data were analyzed using multiple linear regression analysis using IBM SPSS Statistics. The results of the study indicate that directly store atmosphere has a significant effect on impulse buying in Consumers of Kartasura Mitra Department Store, directly product completeness has a significant effect on impulse buying in Consumers of Kartasura Mitra Department Store, directly sales promotion has a significant effect on impulse buying in Consumers of Kartasura Mitra Department Store, and directly and simultaneously store atmosphere, sales promotion, and product completeness have a significant effect on impulse buying in Consumers of Kartasura Mitra Department Store